Study of Stabilization of Soil with Stone dust, Fly Ash and Coir Fiber (International Journal of Innovative Research in Engineering & Management, 2022)
In this paper, the individual as well as  combined use of stone dust, fly ash and coir fibre in the soil  stabilisation is investigated. Fly ash and stone dust was nixed  in the soil at individual percentage varying from 5% to 20%  and coir fibre was mixed with percentage varying from 0.5%  to 2%. Five different samples of each replacement were  made at different percentages based on the individual results  the five different samples with combination of stone dust, fly  ash and coir fibre was made and tested for optimum moisture  content, maximum dry density, california bearing ratio and  unconfined compressive strength. The values of all testes  performed by mixing soil withstone dust, fly ash and coir  fibre was then compared with soil sample and it was found  that mix of soil with up to coir fibre 2%, fly ash 15% and  stone dust 20% gives maximum value of dry density, soil  mix with coir fibre 1%, fly ash 20% and stone dust 20% has  given maximum cbr value 24.52 and maximum ucs value  168.59 was found with mixture of soil with coir fibre 2%, fly  ash 15% and stone dust 20%.
Keywords: Soil; Coir Fibre; Stone Dust; Fly Ash; Soil Stabilization; CBR